New species of Boreofairchildia Wagner & Stuckenberg and Laurenceomyia Wagner & Stuckenberg (Diptera: Psychodidae: Bruchomyiinae) from Brazil - Dos Santos, Claudiney Biral; Brazil, Reginaldo Peçanha; Pinto, Israel De Souza (Zootaxa, 2021)
Two new species of Bruchomyiinae Macquart from Brazil are described and illustrated. Laurenceomyia peixotoi Santos, Brazil & Pinto sp. nov. to Amazon Forest and Boreofairchildia alexanderi Santos, Brazil & Pinto sp. nov. to Atlantic Forest.